The Role of Religion on Food Consuming Issue Developing Theological-Philosophy Concept of Food Through Al Qurâ€™an - Prasetiyo, Joko Roby (SHAHIH: Journal of Islamicate Multidisciplinary, 2020)
This paper discusses the role of religion in responding the negative effects that arise as a result of human relationships with eating activities. Food borne diseases, environmental damage, uneven food supply are some examples of the negative effects that arise as a result of human feeding activities. Religion as the dominant element in shaping human behaviour, is expected to provide solutions to above problems. The solutions are by providing a framework of meaning that can form the behavior of its adherents. So that in interaction with food produces a proportional relationship between God, humans, and nature.This research is descriptive-analytical using the interpretation approach of critical discourse analysis through Qur'anic verses that use the food term and its derivation, namely:Â á¹¬a'Äm, 'Â Akl,Â GizÄun,Â MÄidah, andÂ SyarÄb. At Last, it will be built anearthly concept of food that is theologically-philosophically.Â